Upper Bound for the Energy of the Starlike Trees - Arrizaga-Zercovich, R (IOP Publishing Ltd, 2021)
The energy graph was defined by Gutman, in 1978, as the sum of the absolute values of the eigenvalues of the adjacency matrix. In this work, we obtain a upper bound for the energy of a starlike tree. This bound is obtained in function of the number of vertices and the maximum degree of the vertices. © 2021 Institute of Physics Publishing. All rights reserved.